PELAKSANAAN PELATIHAN HONDA SERVICE EXCELLENCE (HSE) PADA PT PRABU PENDAWA MANUNGGAL DEPOK. - Asrah Tandirerung Ranteallo; Niken Herawati; Bela Rizki Lestari (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2021)
Abstract The Implementation Of Honda Service Excellence (HSE) Training at PT Prabu Pendawa Manuggal, Depok. Employee training extremely related to performance results. Therefore, it takes some training to assess and measure the employee performance. Employee training have an aim that employee have knowledge, abilities and skill which according to their job. The method used by PT Prabu Pendawa Manunggal is Off The Job Training. With the training Honda Service Excellence, a company able to have a qualified employee of providing services to customers. Because in such training implementation, employee trained to be provider service excellence, able to improve their productivity, etc. The result of employees performance will be different with others company which not doing training implementation compared with the implementing. The research method used by descriptive qualitative analysis. From the discussion can concluded that the training implementation Honda Service Excellence (HSE) the PT Prabu Pendawa Manunggal, Depok has already well, it is seen from performance and discipline of employees. Keywords: Training